Seroprevalence of melioidosis among small ruminants in Foster Farm Programme of Faculty of Veterinary Medicine, Universiti Putra Malaysia - Balakrishnan, Thiviya (2017)
Melioidosis is a saprozoonosis, tropical disease caused by Burkholderia pseudomallei which is a ubiquitous soil saprophyte, facultative anaerobic bacteria, non-spore forming, and motile Gram- negative bacillus with bipolar staining, oxidase positive bacteria. This disease can be commonly found in domesticated animals such as sheep, goats, pigs, and other affected species such as cattle, buffaloes, horses, deer, dogs, cats, primates, birds, tropical fish, reptiles and humans. It has public health concern as it is a zoonotic disease and the disease is also a significant animal health problem leading to chronic debility that reduces the productivity of animals. The study farms were selected from the Foster Farm Programme under Faculty of Veterinary Medicine, UPM. In this study, 100 animals from each species comprises of caprine and ovine were sampled. Blood samples were taken and processed for serology test, Complement Fixation Test (CFT). Complement fixation test opted for qualitative determination of immunoglobulin G, IgG antibodies against Burkholderia pseudomallei, whereby the antigen used in this test is prepared by Serology Unit of Veterinary Research Institute Ipoh, Perak. A survey with a set of questionnaire was given to each farm to identify the risk factors related to melioidosis. The data was analysed based on the prevalence rate. Out of 100 goat samples, 1 sample (1%) was positive for antibodies against Burkholderia pseudomallei while all the sheep samples were negative (0%) for the antibody. The positive sample from the goat had 0% end point whereby it has a score of +4 of complete button formation. All the negative results shows 100% end point with full lysis, thus no button formation. In addition, analysis of the questionnaire revealed that all the farms supplies treated water to their farm animals except vary in management system; few practices semi-intensive and intensive farming. As a conclusion, the seroprevalence rate of melioidosis is very low among small ruminants under the Foster Farm Programme of Faculty of Veterinary Medicine, UPM.